eggNOG 5.0: a hierarchical, functionally and phylogenetically annotated orthology resource based on 5090 organisms and 2502 viruses - Huerta-Cepas, Jaime; Bork, Peer (Nucleic acids research, 2019)
Abstract. eggNOG is a public database of orthology relationships, gene evolutionary histories and functional annotations. Here, we present version 5.0, featuri
Published: 12 November 2018
Gesehen am 21.06.2019